2017
DOI: 10.1186/s12986-016-0159-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of adipose tissue in response to fasting and refeeding in male mice

Abstract: BackgroundFasting is the most widely prescribed and self-imposed strategy for treating excessive weight gain and obesity, and has been shown to exert a number of beneficial effects. The aim of the present study was to determine the exact role of fasting and subsequent refeeding on fat distribution in mice.MethodsC57/BL6 mice fasted for 24 to 72 h and were then subjected to refeeding for 72 h. At 24, 48 and 72 h of fasting, and 12, 24, 48 and 72 h of refeeding, the mice were sacrificed, and serum and various ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 52 publications
(71 reference statements)
6
34
1
Order By: Relevance
“…For instance, between Phases I and III we found decreasing expression levels of Nrg4, Lep and Ucp1 in psWAT, decreasing expression levels of Reg1 in STM, and increased expression of Egr1, Fam107a, Map3k6, and Mt1 in the LIV ( Fig. 2c; Additional file 5: Table S4), consistent with previous STF studies in rodents [11,20,[29][30][31][32]. In sum, by allowing the similarity of HVGs among the samples to drive their clustering in an organ-specific manner, we were able to detect differential temporal effects of STF on the transcriptional dynamics across multiple organs.…”
Section: Transcriptome Profiling Across Multiple Organs In the Fastedsupporting
confidence: 90%
“…For instance, between Phases I and III we found decreasing expression levels of Nrg4, Lep and Ucp1 in psWAT, decreasing expression levels of Reg1 in STM, and increased expression of Egr1, Fam107a, Map3k6, and Mt1 in the LIV ( Fig. 2c; Additional file 5: Table S4), consistent with previous STF studies in rodents [11,20,[29][30][31][32]. In sum, by allowing the similarity of HVGs among the samples to drive their clustering in an organ-specific manner, we were able to detect differential temporal effects of STF on the transcriptional dynamics across multiple organs.…”
Section: Transcriptome Profiling Across Multiple Organs In the Fastedsupporting
confidence: 90%
“…Changes in metabolism, distribution and cellularity of adipose tissue is dependent on intrinsic factors such as age, as well as extrinsic factors such as overnutrition. 2,28 We aimed to study how HFD affects adipose tissue dynamics in relation to age. To this effect, we fed mice of various ages (young (8 weeks), adult (16 weeks), middle aged (28 weeks), old (51 weeks) and very old (83 weeks)) chow or HFD for 4 days and labeled proliferating preadipocytes by administering EdU in the drinking water (Schema in Figure 1A).…”
Section: Age Dependent Altered Reaction Of Adipose Tissue To Overnutrmentioning
confidence: 99%
“…2,[4][5][6][7][8][9] Conversely, removal of HFD was shown to reverse most of these changes. 2,10,11 For some time it was believed, that the total number of fat cells is set during adolescence and a change of fat mass in adults is exclusively caused by hypertrophy. 12,13 However, it was recently demonstrated that hyperplasia plays an important role in obesity and that the ability for an increase in adipocyte number persists for lifetime even after severe weight loss.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations